Cross‐Coupling of Heteroarenes by CH Functionalization: Recent Progress towards Direct Arylation and Heteroarylation Reactions Involving Heteroarenes Containing One Heteroatom. Issue 1 (15th January 2014) - Rossi, Renzo; Bellina, Fabio; Lessi, Marco; Manzini, Chiara
Abstract In recent years, transition metal‐catalyzed direct (hetero)arylation reactions of heteroarenes with (hetero)aryl halides and pseudohalides have received significant attention as eco‐friendly and economic alternatives to classical methods for the construction of heteroaryl‐(hetero)aryl CC bonds by transition metal‐catalyzed cross‐couplings involving the use of stoichiometric amounts of organometallic reagents. This critical review with 430 references covers the results obtained in the period January 2009 to February 2013 in the area of the transition metal‐catalyzed direct inter‐ and intramolecular (hetero)arylation reactions of heteroarenes containing one heteroatom. Particular attention has been given to illustrate chemo‐ and site selectivity aspects of these reactions as well applications of these CC bond forming reactions in the synthesis of pharmaceutically relevant compounds, natural products and their analogues and precursors. The most recent advancements into the mechanism(s) of these reactions have also been briefly reported. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>